2013
DOI: 10.3758/s13420-013-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

In search of consolidation of short-term memory in nonhuman animals

Abstract: Wixted (Annual Review of Psychology, 55, 235 – 269, 2004) has argued that forgetting is due to consolidation failure. Previous research with humans and nonhuman animals has reported evidence for consolidation in intermediate or long-term memory (LTM). The present study examines whether consolidation occurs in short-term memory in pigeons. Delayed matching-to-sample accuracy was reduced when retroactive interference (an extraneous task in Experiment 1 or houselight illumination in Experiment 2) was interpolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Although later research by Grant (1988) found that houselight illumination disrupted delayed matching accuracy when it occurred either in the first or the last 2 s of a 5 s delay, the disruption was greater when it occurred later in the delay. Recently, in a parametric study, Calder and White (2014) varied the duration and the location of the houselight illumination and found that illumination of the houselight was disruptive primarily when it appeared just prior to presentation of the comparison stimuli. This finding suggests that illumination of the houselight has little effect on sample memory, but rather it may serve as a source of distraction, perhaps by illuminating other stimuli in the chamber.…”
Section: Interference Effectsmentioning
confidence: 99%
“…Although later research by Grant (1988) found that houselight illumination disrupted delayed matching accuracy when it occurred either in the first or the last 2 s of a 5 s delay, the disruption was greater when it occurred later in the delay. Recently, in a parametric study, Calder and White (2014) varied the duration and the location of the houselight illumination and found that illumination of the houselight was disruptive primarily when it appeared just prior to presentation of the comparison stimuli. This finding suggests that illumination of the houselight has little effect on sample memory, but rather it may serve as a source of distraction, perhaps by illuminating other stimuli in the chamber.…”
Section: Interference Effectsmentioning
confidence: 99%
“…Subsequent studies demonstrated that not only monkeys [11 ,12] but also pigeons [13,14] and rats [15][16][17][18][19] can also perform dualtasks in various conditions and also exhibit dual-task interference effects analogous to those in humans (Table 1). Recently, Smith et al [12] applied the dual-task method to examine whether or not metacognitive process can be dissociated from perceptual-level process using monkeys.…”
Section: Behavioral Analyses Of the Dual-task Interference Effect In mentioning
confidence: 99%
“…Combination of tasks Behavioral studies Moise [9] Monkey DMS a + simple reaction time task Washburn and Astur [10] Monkey DMS + overt OT b or numerical judgment task Basile and Hampton [11 ] Monkey DMS + motor, image perception, or image classification task Smith et al [12] Monkey DMS or DMP c + perceptual confidence judgment Kendrick and Rilling [13] Pigeon DMS + VI d , EXT e , or DRO f schedule Calder and White [14] Pigeon DMS + VI schedule Maki et al [15] Rat 8-arm WS g radial maze + 4-arm WS h radial maze Beatty and Shavalia [16] Rat 8-arm WS radial maze + 8-arm WS or WS radial maze Roberts [17] Rat 8-arm WS radial maze + 8-arm WS radial maze Cook and Brown [18] Rat 12-arm WS radial maze + 12-arm WS radial maze Jarrard and Elmes [19] Rat 12-arm WS radial maze + 4-arm WS radial maze Harper et al [45] Rat SPR i in 12-arm maze + food consumption Neurophysiological studies…”
Section: Speciesmentioning
confidence: 99%
“…The goal of the present experiments was to investigate chimpanzees' memory processing in a short-term memory [28] reward-location paradigm that did not require training. Chimpanzees were presented with a target task, which involved remembering a reward location (e.g., left container), followed by the presentation of an interference task-requiring the recollection of a different reward location (e.g., right container).…”
Section: Introductionmentioning
confidence: 99%